Turkey’s Environmental Legislation: Formation and Development Characteristics - ZHANBAZ, Mustafa (Journal of Advanced Research in Law and Economics; Vol 7 No 5 (2016): Vol 7, No 5(2016): JARLE Volume VII, Issue 5(19), Fall 2016, 2016)
The article presents scientific-methodological and historical-legal analysis of Turkey’s legislation concerning the environmental protection. At the modern stage, the environmental law focuses on a detailed study of the history of environmental legislation development. Environmental degradation in Turkey has a negative impact on the people’s needs and conflicts with interests of the population, raising socio-economic tensions on regional and country’s levels. Failing to manage social processes, people may turn the environment into a place, unfit for human existence, while ignorance of the need to restore the environment can result in devastating processes that can disrupt the progressive development of the civilization. The research aims to examine development and formation features of the fundamentals of environmental protection legislation in Turkey, taking into account the relevant historical experience of the modern law-making. The research is based on functional and system-structural approach to the scope of study, as well as methods of historical-legal and comparative legal analysis used throughout working on the paper. The findings of the research revealed the continuity in Turkish environmental legislation, which stems from customary law and national traditions. The formation of the Turkish legislation on environmental protection can be divided into three stages. The historical and legal analysis of the Turkish legislation on environmental protection focusing on its development to the modern state allowed the author to identify the main directions of this process. Taking into account the experience of European countries and Japan, the author suggests legally formalizing and implementing a regulation mechanism to compensate for the damages from environment pollution in Turkey.
Keywords: legal regulation, environmental protection, human right to a healthy environment